2016
DOI: 10.1038/srep21411
|View full text |Cite
|
Sign up to set email alerts
|

Truncated yet functional viral protein produced via RNA polymerase slippage implies underestimated coding capacity of RNA viruses

Abstract: RNA viruses use various strategies to condense their genetic information into small genomes. Potyviruses not only use the polyprotein strategy, but also embed an open reading frame, pipo, in the P3 cistron in the –1 reading frame. PIPO is expressed as a fusion protein with the N-terminal half of P3 (P3N-PIPO) via transcriptional slippage of viral RNA-dependent RNA polymerase (RdRp). We herein show that clover yellow vein virus (ClYVV) produces a previously unidentified factor, P3N-ALT, in the +1 reading frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 68 publications
2
47
0
Order By: Relevance
“…Previously, we reported that in the susceptible pea line PI 250438 infected with Cl-90-1 Br2 or ClNo.30, P3N-PIPO of Cl-90-1 Br2 could be detected, but the amount of P3N-PIPO of Cl-No.30 was below the level of detection when tested by using an antibody against the PIPO peptide (7). Furthermore, we showed that the amount of P3N-PIPO produced from the P3 cistron of Cl-No.30 is significantly smaller than that of Cl-RB in an in vitro translation system using MM2 dL (an extract derived from A. thaliana MM2d cells) and wheat germ extract (7,13). In this study, we showed evidence that the P3 cistron of ClNo.30 produced less P3N-PIPO protein than did Cl-RB in vivo in agroinfiltrated N. benthamiana leaves (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we reported that in the susceptible pea line PI 250438 infected with Cl-90-1 Br2 or ClNo.30, P3N-PIPO of Cl-90-1 Br2 could be detected, but the amount of P3N-PIPO of Cl-No.30 was below the level of detection when tested by using an antibody against the PIPO peptide (7). Furthermore, we showed that the amount of P3N-PIPO produced from the P3 cistron of Cl-No.30 is significantly smaller than that of Cl-RB in an in vitro translation system using MM2 dL (an extract derived from A. thaliana MM2d cells) and wheat germ extract (7,13). In this study, we showed evidence that the P3 cistron of ClNo.30 produced less P3N-PIPO protein than did Cl-RB in vivo in agroinfiltrated N. benthamiana leaves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that P3N-PIPO was detected in Cl-RB-infected plants but was below the level of detection in Cl-No.30-infected plants of a susceptible pea cultivar, PI 250438, indicating that the level of P3N-PIPO from Cl-No.30 is significantly lower than that of P3N-PIPO from Cl-90-1 Br2 (7). The same difference was observed when P3N-PIPO was produced from the P3 cistron of each virus by using an in vitro translation system with an A. thaliana cell-free system and wheat germ extract (7,13). In this study, we compared the accumulation of Cl-No.30 P3N-PIPO with that of Cl-RB P3N-PIPO in a transient-expression system, agroinfiltration in N. benthamiana leaf tissues.…”
Section: P3 Of CLmentioning
confidence: 94%
See 3 more Smart Citations